A Novel Synthesis of Fe3O4@SiO2@Au@Porous SiO2 Structure for NIR Irradiation-Induced DOX Release and Cancer Treatment. Issue 1 (14th February 2020) - Yang, Meng; Yang, Wenhua; Chen, Liang; Ding, Mingjian; Li, Chenhao; Shi, Dongliang
Doxorubicin (DOX) alone or in combination has been widely used for numerous cancers, including breast, lung, bladder, and so on. In this article, a core/shell/shell structured Fe3 O4 @SiO2 @Au@porous SiO2 particles for the drug delivery and release of DOX was demonstrated, with the aid of near-infrared irradiation. Fe3 O4 was used to direct the transportation and delivery of the drug-loaded composite to the target tissues and organs under an external magnetic field, the first layer of SiO2 was used for Au nanoparticle attachment, Au acted as the agent for light–thermal conversion, and the porous SiO2 was used to load DOX. The morphology of the nanoparticles was studied by transmission electron microscopy, and the porous structure was characterized by N2 adsorption/desorption curves. The drug delivery system displayed high drug loading capacity, and the release behavior was largely impacted by the environmental pH. Furthermore, the cytotoxicity of Fe3 O4 @SiO2 @Au@porous SiO2 and DOX loaded Fe3 O4 @SiO2 @Au@porous SiO2 was studied through in vitro 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide cell viability assay.